The Influence of Green Intellectual Capital on Sustainable SMEs - Styaningrum, Farida; Wahjoedi, Wahjoedi; Utomo, Sugeng Hadi; Mukhlis, Imam; Sulistyowati, Nur Wahyuning; Fuat’dah, Devit Anisatul; Nugrahaningtyas, Andien; Qofifah, Salmaa Nur (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2023)
Environmental degradation is a global issue that invites attention from various groups, including small and medium enterprises (SMEs). To preserve the environment and build a sustainable business, it is necessary to optimize environmentally friendly resources. Green intellectual capital, which includes green human capital, green structural capital, and green relational capital, can be practiced by SMEs in maintaining sustainable business. The research aims to empirically prove the influence of green intellectual capital on sustainable SMEs. The research adopted a quantitative method with a self-administered survey. The research sample consisted of 157 respondents who were SMEs in Madiun of Indonesia. Furthermore, the data were analyzed using Smart-PLS 3.0 to prove the hypothesis. The results show that green human capital and green relational capital do not have a significant influence on sustainable SMEs. Meanwhile, green structural capital has a significant influence on sustainable SMEs. This implies that SMEs must pay attention to the internal organizational management system in practicing environmentally businesses.